An analysis of cell cycle alterations and apoptosis induced by etoposide and hyperthermia - Lim, Chang-Uk, author; Fox, Michael D., advisor; Bedford, Joel S., committee member; Fahrney, David E., committee member; Laure, Susan M., committee member (Colorado State University. Libraries, 2004)
Many toxic agents cause cells to undergo apoptosis, but different agents may cause cells to undergo apoptosis in different phases of the cell cycle. In addition, cells may undergo cell cycle delays after treatment with toxic agents. I developed three models to analyze apoptosis and the cell cycle; a cell cycle progression model, a cumulative apoptotic index (CAI) estimation model, and an apoptotic quotient calculation. CAI was calculated by measuring apoptotic index (AI) at multiple time points after a treatment. These models allow for identification of the cell cycle distribution of apoptotic and non-apoptotic cells and to determine whether cells in a particular phase of the cell cycle are preferentially sensitive to apoptosis. I have tested these models with two different cell lines: HL-60 cells and HCW-2 cells, a mutant cell line derived from HL-60 cells that is resistant to apoptosis. Cells were treated with 6.25 μg/ml etoposide for 3 hr or heated at 45.0 °C for 15 or 30 min and analyzed at various times later. HL-60 cells treated with etoposide were resistant to apoptosis in G1 and G2/M phases but were sensitive to apoptosis in S phase. Etoposide-treated HL-60 cells also were delayed in G1 and G2/M phases. HCW-2 cells treated with etoposide did not undergo apoptosis but experienced an early S phase arrest, late G1 phase arrest, continuous G2/M phase block and increasing Tpot. HL-60 cells heated at 45.0 °C for 15 min had four phases of apoptosis and 34.8 % cumulative apoptotic cells while cells heated for 30 min had three phases of apoptosis and 93.6 % cumulative apoptotic cells. When the heat dose was increased from 15 to 30 min, CAI, Tw, (time-window) and Tl (length of each phase) were also increased. The increase in CAI and Tl, with a larger heat dose resulted in the production of more apoptotic cells and an increase in Tw, which means that the substrate for the assay existed longer for a greater heat shock. In conclusion, these techniques can provide a more detailed understanding of the kinetics of apoptosis, cell cycle progression and delays simultaneously from TUNEL histograms.
Keywords: cellular biology; molecular biology